The KTB superdeep borehole: petrography and structure of a 9-km-deep crustal section - de Wall, Helga; et al. (Geologische Rundschau, 1997)
The KTB boreholes that were drilled from 1989 to 1994 near Windischeschenbach, NE Bavaria, penetrated rocks of the Zone Erbendorf-Vohenstrauss (ZEV). The upper and lower sections of the 9101-m-deep profile are mainly composed of gneiss units and variegated units. Metabasic units constitute mainly the middle section. Geochemical data suggest their derivation from oceanic crust. All rocks are probably pre- to early Ordovician in protolith age. They underwent early Devonian MP metamorphism. Relics of preceding HP metamorphism are preserved in metagabbros. In contrast to the conditions of the Mesozoic (mainly Cretaceous/Tertiary) faulting the P-T conditions of MP metamorphism, the cooling ages and the late-Variscan graphite-bearing prehnite-actinolite facies mineralization show no significant depth-dependent gradients. This can be explained by Mesozoic supracrustal stacking.
UnivIS-Import:2015-03-05:Pub.1997.nat.dgeo.IGM.c3tekt.thektb